Faces in disguise. Masks, concealment, and deceit. - Gramigna, Remo (Topoi: An International Review of Philosophy, 2022)
The present study investigates and thematizes the interrelation between face masking, concealment, and deceit. It starts from the premise that the significance of disguise and deceit in the history of ideas should be reversed as these methods of the management of human appearance are not only regarded as coercive methods to manipulate and exert power over others but also as tactics skillfully used by the weak in order to outmaneuver those who are in a position of power. The study traces the matrix of simulation and dissimulation as forming the structure of deceit, it reviews some of the main theories of disguise within the field of semiotics, and it singles out two main dimensions of disguise, one geared upon dynamism and the other based on the static features of the face. This study suggests that classifications of masks elaborated in semiotic theory hitherto are useful but insufficient to encompass the full scope of such phenomenon. For this reason, the study provides a new typology of masks.